FACTORES QUE INCIDEN EN LA INFRACCIÓN DE LA LEY PENAL POR PARTE DE LOS ADOLESCENTES EN EL MUNICIPIO DE CHIQUINQUIRÁ (2019)
The increase of admission to specialized centers for teenagers who break the criminal law for trafficking, theft, and carnal access, among other crimes, has become a problem of great concern for the society of Chiquinquirá, due to the fact that no legal response has been found to the criminal problem. The objective of this research was to analyze the social, economic and cultural factors that affect the commission of crimes by adolescent offenders of the Criminal Responsibility System for Adolescents in the municipality of Chiquinquirá, department of Boyacá (Colombia). From the field of legal sociology and under the theoretical approach of the same, a particular aproximation was made to the evaluation of quality of life and theorization on basic social justice.